Shifting the service referral paradigm using community-based second responders: examining weapon use in intimate partner violence - Rubenstein, Batya Y. (Journal of family violence, 2021)
To address a rise in intimate partner violence (IPV) related homicides, Cincinnati Police Department (CPD) partnered with Women Helping Women (WHW), a community, gender-based violence prevention organization to create the Domestic Violence Enhanced Response Team (DVERT). Second responders are sent out to the scene of IPV police calls to better address the needs of survivors and connect them with services. The aim of this study is to assess how calls involving weapons differed from those that did not. The sample included 1253 calls from August 2018 to January 2020, which were then categorized by whether or not the incident included a weapon. A series of bivariate analyses were conducted to assess for differences between groups in perpetrator and survivor characteristics, harm incurred, criminal justice responses, and referrals for services. There were significant differences in perpetrator characteristics between weapon involvement groups. Perpetrators in the weapon involvement group were more likely to have access to weapons; history of physical violence, verbal or mental abuse; substance abuse problems, and mental illness. Black women were disproportionately more likely to have a weapon used on them. The criminal justice system did not differ significantly in their response to cases involving weapons. However, survivors of weapons related cases were overall more likely to receive service referrals. Findings suggest a need for community-based second responder programs to partner with police departments to address the multitude of needs for survivors given the lethality of these incidents.